Analisis Karakter Pelanggan Jasa Katering Untuk Keperluan Hajatan di Sidoarjo - Preiselia Constella Yudita Putri; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2022)
The goal of this study was to evaluate the behavior of customers who use catering services in Sidoarjo. The type of research employed is a description experiment with multiple variations in the source's behavior. In order to process the data for this study, frequency tables, bar charts, and cross-tabulation were used. In this study, convenience samples were used in the process of gathering resource people. This study relies on the results of studies separated into male and female speakers. based on the speakers' work and the age-frequency distribution. Buffets are often utilized types of catering services based on the maxim that "the most is efficient." The side that frequently encourages speakers is friends and other speakers that utilize catering services to host events. The resource person used CV CATHLEA CATERING, and the resource person learned about the catering from friends. The people with the most resources regularly utilize catering services and are pleased with their utilization. The majority of speakers were satisfied since it was in accordance with the customer's desires.